2001
DOI: 10.1007/s001670100197
|View full text |Cite
|
Sign up to set email alerts
|

A radiographic analysis of the relationship between the size and shape of the intercondylar notch and anterior cruciate ligament injury

Abstract: Notch-view radiographs were obtained from 108 persons with anterior cruciate ligament (ACL) injuries (55 women, 53 men) and 186 with intact ACL (94 women, 92 men). Notch width, femur width, and notch width index were determined from each of the 294 radiographs. The notch was also categorized as either A-shaped or non-A-shaped. Intrarater and interrater reliability ranged from 0.82 to 0.99 for notch width and femur width, respectively. Reliability within and between raters for the classification of notch shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
110
1
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 22 publications
4
110
1
9
Order By: Relevance
“…Our finding that a lower NWI index may predispose to ACL injury in the paediatric population is in accordance with previous studies looking at young adult populations [2][3][4][5][6][7]20]. While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that a lower NWI index may predispose to ACL injury in the paediatric population is in accordance with previous studies looking at young adult populations [2][3][4][5][6][7]20]. While there is still disagreement in the literature as to whether variations in notch geometry related to differences in gender or limb dominance, play a contributing role in ACL injuries, we did not find a difference in NWI with respect to gender, involved side, mechanism of injury or type of sport engaged in at the time of injury [7,12,13,18,21,22].…”
Section: Discussionsupporting
confidence: 93%
“…This difference may be caused by different imaging techniques used for the evaluation of NWI. Two studies measuring NWI using MRI [8,21] have shown much higher values for normal adult populations than values reported in radiographic studies [2][3][4][5][6][7]20].…”
Section: Discussionmentioning
confidence: 88%
“…43 Ireland and colleagues reported that females have a higher proportion of A-shaped notches and both notch width and notch width index were found to be significant indicators of ACL injuries. 11 They suggested that regardless of gender, individuals with smaller notch dimensions are at greater risk of ACL injury than those with larger notches. 11 Finally, in vivo studies on joint laxity during anterior translation and internal rotation showed increased joint laxity in females when compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…11 They suggested that regardless of gender, individuals with smaller notch dimensions are at greater risk of ACL injury than those with larger notches. 11 Finally, in vivo studies on joint laxity during anterior translation and internal rotation showed increased joint laxity in females when compared to males. 19,23,24 The results from our study add that increased knee joint laxity in females occurs with external tibial rotation as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation